ANALISIS KETERSEDIAAN, KETERJANGKAUAN DAN PEMANFAATAN PANGAN DALAM MENDUKUNG TERCAPAINYA KETAHANAN PANGAN MASYARAKAT DI PROVINSI JAWA TENGAH - Sri Pujiati; Amelia Pertiwi; Churun Cholina Silfia; Dewa Maulana Ibrahim; Siti Hadiyati Nur Hafida (Jurnal Sosial Ekonomi Pertanian, 2020)
AbstractFood security becomes an aspect that needs to be considered, especially when the population and degradation of agricultural land are increasing. Many variables that affect the measurement of the food security index, and what is often used is the availability, affordability, and utilization of food. This study aims to determine the effect of food availability, affordability, and utilization variables on the food security index. This study uses a correlational design and multiple regression analysis techniques. All regions in Central Java Province were the objects of this study, there are 35 districts/cities. The results from this study showed that the three variables did not significantly influence the increase of the food security index. The result shows that the current food security index has been influenced by other variables.  Therefore, the government needs to examine more closely the new variables that affect the food security index in order to develop a strategy to improve the food security index in Central Java Province, especially in the era of the industrial revolution 4.0. Keywords: Food Security Index; Food Affordability; Food Availability; Food Utilization